Tres Homes Dins D'una Barca (Sense comptar-hi el gos) - Jerome, Jerome K. (Jerome Klapka), 1859-1927; Mustieles, Jacinto María, 1887- (Salt Lake City, UT : Project Gutenberg, 2009)
"Tres Homes Dins D'una Barca (Sense comptar-hi el gos)" by Jerome K. Jerome is a humorous novel published in 1889. Three friends and a dog embark on a two-week boating holiday up the Thames, camping along the way from Kingston to Oxford and back. What begins as a respite from "overwork" becomes a comedy of mishaps and misadventures. The narrator shares witty observations about fishing, boating blunders, and the peculiarities of Victorian life, blending travel commentary with timeless humor that still feels fresh today. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Three_Men_in_a_Boat
Release date is 2009-09-09
Keywords: Young men -- Travel -- England -- Thames River -- Fiction; Boats and boating -- England -- Thames River -- Fiction; Dogs -- Fiction; Humorous stories, English; Thames River (England) -- Fiction; Male friendship -- Fiction